Impact of identity politics on education in Pakistan: A comparison between Balochistan and Punjab. (November 2018) - Nasser, Ammna; Kyriazi, Tenia; Paris, Cody Morris; Ahmad, Mahine
This research article examines the impact of ethnic identity-based politics on education in Pakistan through in-depth interviews with young professionals from Balochistan and Punjab. The findings suggest that the Punjabi-dominated power structure results in an unequal allocation of financial resources, whereby Balochistan lacks the financial resources to invest in education development. In addition, political instability caused by unprecedented ethnic strife contributes towards poor-quality education, which, as a result, adversely impacts a Balochi's future course of life. On the other hand, Punjabis are at an advantage in the public arena because of their robust educational foundation.